Influence of Blood Metabolites on Ovarian Rebound in Postpartum Sahiwal Cows - Uppal, Mithilesh; Awasthi, Manoj Kumar; Poyam, Mahesh Ram; Mishra, Girish Kumar; Verma, Manisha; Parveen, Kaiser (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Present investigation was carried out to study the influence of blood metabolites, viz., glucose and NEFA on ovarian rebound inpostpartum Sahiwal cows. Advance pregnant Sahiwal cows (n=14) maintained at Bull Mother Experimental Farm at Anjora, Durg (CG),India were selected and divided into two Groups, Group I comprised of animals (n=7) with BCS ≥ 2.75 and that of Group II comprised ofanimals (n=7) with average BCS < 2.75 at one week before parturition. Trans-rectal ultrasound scanning of ovaries was accomplishedin animals of both groups on alternate days from 21 to 51 days postpartum to record the development of dominant follicles (DF).Animals of Group-I without DF recorded higher pre-partum BCS than those with DF (n=3). Non-significant differences were recordedin mean serum glucose concentration between animals of Group-I and Group-II during all days of observation. Significant differenceswere (p
Keywords: BCS; Dominant follicle; Glucose; NEFA; Ovarian rebound; Sahiwal cows